What Factors Influencing Export Quantity for Indonesian and Philippine Coconut Oil - Rido Tanago; David Kaluge (Jurnal Ekonomi dan Studi Pembangunan, 2019)
The coconut oil as main product of coconut is not competitive anymore compared to palm oil. Indonesia and Philippines are two biggest producers of coconut. This paper study whether the price of coconut oil, the price of crude palm oil, the price of virgin olive oil, and gross domestic product influence the quantity export for Indonesian and Philippines coconut oil. Using multiple linear regression, the results indicate that in the Philippines the variables used in the study (price of coconut oil, price of crude palm oil, price of virgin olive oil and Philippines GDP) have no significant impact on export quantity for Philippines. While coconut oil export quantity for Indonesia is significantly influenced by Indonesia GDP.Keywords: export of coconut oil, crude palm oil, virgin olive oil, gross domestic product